The labor market consequences of regulating similar occupations: The licensing of occupational and physical therapists - Jing Cai; Morris M. Kleiner (W.E. Upjohn Institute for Employment Research, 2016)
This study shows the influence of occupational licensing on two occupations that provide similar services: occupational therapists and physical therapists. Most of the tasks for these two occupations differ, but several jobs overlap, and individuals in both occupations could have legal jurisdiction over these tasks. We empirically examine how these two occupations interact with one another in the labor market on wage determination and employment. Unlike previous studies, our study examines two occupations that are female dominated both within the professions and among its leadership. Our results show that occupational licensing can raise the wages of members of both occupations, but the duration of state occupational licensing statutes is the dominant influence on wage determination. Occupational licensing is also associated with a reduction in annual hours worked and in the relative numbers of members in each of the professions. Moreover, the ability of physical therapists to have direct access to patients is associated with a reduction in hourly earnings for occupational therapists, suggesting some substitution for certain service tasks across the two occupations. The ability of these two occupations to be both complements to and substitutes for one another provides new evidence on how the growing number of regulated occupations that are similar interact and influence one another.
Keywords: J44; J31; J38; J88; 330; Occupational licensing; wage determination; interaction of occupations